TIPIFICACIÓN DEL DELITO DE TRANSMISIÓN CONSCIENTE DEL VIRUS DE INMUNODEFICIENCIA HUMANA VIH, EN EL CÓDIGO ORGÁNICO INTEGRAL PENAL, PARA GARANTIZAR EL DERECHO A LA VIDA, INTEGRIDAD Y SALUD DE LAS PERSONAS - Cañar Sarango, Joseth Andrey (2020)
The present thesis entitled: “Typification of the crime of conscious transmission of the human immunodeficiency virus HIV, in the Organic Comprehensive Criminal Code, to guarantee the right to life, integrity and health of people", refers to the increase in cases of infection of the human immunodeficiency virus, which is largely due to many carriers, namely, having all the human rights of the Constitution of the Republic of Ecuador and that are positive for HIV, for example, the World Health, governments are implemented in their legislation, the penalty of the conscious transmission of HIV, carefully analyzing the Comprehensive Criminal Organic Code reaches the conclusion that there is no specific criminal type that solves this type of social problems, by This refers to a crime of conscious transmission of the Human Immunodeficiency Virus (HIV). This is the objective of redirecting the index transmission of the human immunodeficiency virus, preventing increasing social stigma and that of people who acquire in this way. On the other hand, the materials and methods that contributed to the development of the present investigation are applied, as well as the respective interviews and surveys, which have been used to propose the legal reform project to the Organic Comprehensive Criminal Code, so that rights The life, integrity and health of people who have been infected, in a conscious way, the human immunodeficiency virus.